The role of symbiotic algae in the formation of the coral polyp skeleton: 3‐D morphological study based on X‐ray microcomputed tomography. (13th September 2016) - Iwasaki, Shinya; Inoue, Mayuri; Suzuki, Atsushi; Sasaki, Osamu; Kano, Harumasa; Iguchi, Akira; Sakai, Kazuhiko; Kawahata, Hodaka
Abstract: Symbiotic algae of primary polyps play an important role in calcification of coral skeletons. However, the function of the symbiotic algae, including the way they influence the physical features of their host skeleton under various conditions, is not well understood. We used X‐ray microcomputed tomography to observe skeletal shape characteristics in symbiotic and aposymbiotic primary polyps of Acropora digitifera that were cultured at various temperature and p CO2 levels (temperature 27, 29, 33°C; p CO2 400, 800, 1000 µatm). Symbiotic polyps had a basal plate with a well‐developed folding margin supporting the branched skeleton, whereas aposymbiotic ones did not. The features of the folding margin suggest that it might be the initial growth stage of the epitheca. In addition, three‐dimensional (3‐D) morphological measurements made by X‐ray microcomputed tomography show that the branched skeletons of symbiotic primary polyps were taller than those of aposymbiotic ones, suggesting that zooxanthellae in coral primary polyps play a critical role in the height growth of skeletal branches. Furthermore, results of the temperature‐ and p CO2 ‐controlled experiments suggest that global warming might greatly affect the activity of zooxanthellae, whereas ocean acidification might reduce calcification by damaging the coral host itself. Our findings provide new knowledge about the role of zooxanthellae in coral calcification. Key Points: Symbiotic primary polyps produced a skeleton having a basal plate with a well‐developed folding margin Skeletons of symbiotic primary polyps were higher than those of aposymbiotic polyps Global warming may greatly affect the activity of zooxanthellae, and ocean acidification may damage the coral host itself